Análise da mobilidade urbana através de dados da rede de telefonia móvel celular - Araujo, Pablo Andrey Arruda de (2014)
With the economic growth experienced in recent years, many brazilian cities have also encountered problems such as population growth, congestion of vehicles and violence. At the same time, the purchasing power of the population has grown, allowing many of them to purchase new equipment, such as mobile phones, with Brazil surpassed the barrier of a cell phone per inhabitant. This study aimed to examine the feasibility of using computer simulation systems, using data from the mobile telephone network, aiming a system of urban monitoring usig vehicles. The results showed that the higher was the number of vehicles on public streets, most will hit rate with the data from the cellular network using the methodology of Erlang.